Sabbatical Leave Report - Inguanti, Joseph J. (2016)
A study that explores the role of images of the landscape in marketing America to would-be Italian emigrants in the era of the Great Migration (1880-1920).
Keywords: dept.art; faculty_collection; sabbatical_report